Feasibility of a nursing rehabilitation guideline for patients with stroke: evaluating the use by nurses. (June 2013) - Hafsteinsdóttir, Thóra B.; Varekamp, Rudi; Rensink, Marijke; van Linge, Roland; Lindeman, Eline; Schuurmans, Marieke; ,
<x xml:space="preserve">Abstract</x> Purpose: To determine the feasibility of the Clinical Nursing Rehabilitation Stroke-guideline (CNRS-guideline) in the care of stroke patients in terms of the experiences, views and attitudes of nurses towards the guideline and their adoption of the guideline and how often the recommendations were used. Method: A four phase cross sectional design was used. Demographic data were collected from nurses (n=30) and patients (n=105). After each test phase the nurses received questionnaires about their experiences of the guideline including questions about their attitude towards the guideline and adoption of the guideline. Also, how often the recommendations were used was registered. Results: The nurses' general impression of the recommendations scored a median of 6.0. A majority of the nurses indicated that the aims of the guideline were clear, that it provided new insights into stroke care. Among the challenges experienced were lack of knowledge and skills and organizational difficulties. Half of the nurses adopted the guideline and the nurses' attitude towards the guideline scored a median of 6.0. Conclusion: The guideline provides nurses with an important means for evidence based care for patients with stroke. The guideline was feasible for nurses to use but various challenges need ongoing attention when planning implementation.